Assessment of Left Ventricular Ejection Fraction Calculation on Long-axis Views From Cardiac Magnetic Resonance Imaging in Patients With Acute Myocardial Infarction. Issue 43 (October 2015) - Huttin, Olivier; Petit, Marie-Anaïs; Bozec, Erwan; Eschalier, Romain; Juillière, Yves; Moulin, Frédéric; Lemoine, Simon; Selton-Suty, Christine; Sadoul, Nicolas; Mandry, Damien; Beaumont, Marine; Felblinger, Jacques; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: To assess left ventricular ejection fraction (LVEF) accurately, cardiac magnetic resonance (CMR) can be indicated and lays on the evaluation of multiple slices of the left ventricle in short axis (CMRSAX ). The objective of this study was to assess another method consisting of the evaluation of 2 long-axis slices (CMRLAX ) for LVEF determination in acute myocardial infarction. One hundred patients underwent CMR 2 to 4 days after acute myocardial infarction. LVEF was computed by the area-length method on horizontal and vertical CMRLAX images. Those results were compared to reference values obtained on contiguous CMRSAX images in one hand, and to values obtained from transthoracic echocardiography (TTE) in the other hand. For CMRSAX and TTE, LVEF was computed with Simpson method. Reproducibility of LVEF measurements was additionally determined. The accuracy of volume measurements was assessed against reference aortic stroke volumes obtained by phase-contrast MR imaging. LVEF from CMRLAX had a mean value of 47 ± 8% and were on average 5% higher than reference LVEF from CMRSAX (42 ± 8%), closer to routine values from TTELAX (49 ± 8%), much better correlated with the reference LVEF from CMRSAX ( R = 0.88) than that from TTE ( R = 0.58), obtained with a higher reproducibility than with the 2 other techniques (% of interobserver variability: CMRLAX 5%, CMRSAX 11%, and TTE 13%), and obtained with 4-fold lower recording and calculation times than for CMRSAX . Apart from this, CMRLAX stroke volume was well correlated with phase-contrast values ( R = 0.81). In patients with predominantly regional contractility abnormalities, the determination of LVEF by CMRLAX is twice more reproducible than the reference CMRSAX method, even though the LVEF is consistently overestimated compared with CMRSAX . However, the CMRLAX LVEF determination provides values closer to TTE measurements, the most available and commonly used method in clinical practice, clinical trials, and guidelines in ischemic cardiomyopathy. Moreover, LVEF determination by CMRLAX allows a 63% gain of acquisition/reading time compared with CMRSAX . Thus, despite the fact that LVEF obtained from CMRSAX remains the gold standard, CMRLAX should be considered to shorten the overall imaging acquisition and reading time as a putative replacement.